2018
DOI: 10.1016/j.jcct.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue density and volume are related to subclinical atherosclerosis, inflammation and major adverse cardiac events in asymptomatic subjects

Abstract: EAT volume was higher and density lower in subjects with coronary calcium compared to subjects with CCS = 0, with similar EAT volume in CCS<100 and CCS≥100. Lower EAT density and increased EAT volume were associated with coronary calcification, serum levels of plaque inflammatory markers and MACE, suggesting that dysfunctional EAT may be linked to early plaque formation and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
161
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(174 citation statements)
references
References 34 publications
5
161
3
5
Order By: Relevance
“…EAT volume, and more recently attenuation have been increasingly investigated in the literature for associations with cardiac disease 8,[11][12][13][14][15] . Several studies have demonstrated significant cross-sectional relationships www.nature.com/scientificreports www.nature.com/scientificreports/ between EAT and cardiac disease, however a lack of longitudinal data prevents understanding of what therapies or targets may be a modulating factor for EAT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EAT volume, and more recently attenuation have been increasingly investigated in the literature for associations with cardiac disease 8,[11][12][13][14][15] . Several studies have demonstrated significant cross-sectional relationships www.nature.com/scientificreports www.nature.com/scientificreports/ between EAT and cardiac disease, however a lack of longitudinal data prevents understanding of what therapies or targets may be a modulating factor for EAT.…”
Section: Discussionmentioning
confidence: 99%
“…EATd is hypothesised to be a marker of adipose tissue activity, and may even represent a marker of vascular inflammation 8 . As EAT is present in all human anatomy and differentially distributed around the myocardium, it is possible that the activity of EAT may have a greater effect on cardiac and coronary dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,21-23 Goeller M et al, observed that lower EAT and increased EAT volume were associated with coronary calcification, serum levels of plaque inflammatory markers and adverse cardiovascular events, suggesting that dysfunctional EAT may be linked to early plaque formation and inflammation. 24 Several studies suggest the association of epicardial fat with CAD. 25,26 Mahabadi AA et al, nconcluded that epicardial fat is associated with fatal and nonfatal coronary events in the general population independent of traditional cardiovascular risk factors and complements information from cardiac computed tomography above the CAC score.…”
Section: Discussionmentioning
confidence: 99%
“…6 As reported, increased volume and inflammation of EAT are associated with the progression of cardiac dysfunction in obese individual. [16][17][18] However, the alterations of metabolic and functional alterations in EAT have been considered clinically important but are yet to be systematically investigated. Accordingly, in this study, we described Amongst the differentially expressed proteins, we believe that Serpina3 make a prominent link between EAT and HF.…”
Section: Discussionmentioning
confidence: 99%